(untitled) (Revista Venezolana de Salud Pública, 2018)
In accordance with the last editorial of the Venezuelan Public Health Magazine1, we can add that by the year 2018 tuberculosis is emerging as one of the ten (10) main causes of mortality in the world2 presenting a moderate rate of 26.1 in Venezuela. per 100,000 inhabitants. The Delta Amacuro state represents one of the highest caseloads in Venezuela, especially in indigenous populations such as the Warao ethnic group where prevalence has been achieved in children with up to 60% pulmonary tuberculosis in populations such as San Francisco del Guayo in the Orinoco Delta3; also in indians of the Colombian Orinoquía, there have been rising rates of tuberculosis greater than 1% of the population. Among the main causes of this increase are the increase in the resistance of the causative agent to the drugs, the increase in the number of cases of HIV patients, the weakening of the epidemiological surveillance programs, the presence of cases of pulmonary tuberculosis. diagnosed and untreated, delay in the diagnosis, treatment and follow-up of the disease, as well as the persistence of malnutrition and overcrowding which are expressions of economic vulnerability in this group of patients4. Tuberculosis is considered the second cause of death globally and the first among infectious diseases5. On September 18, 2017, the World Health Organization (WHO) published the global tuberculosis report revealing that in 2016 in Venezuela there were 10,952 cases of this disease5, number of cases that has been growing in recent years . For the same year, Venezuela had notified the agency 8,592 cases, which showed that in just 12 months, the number of infected with tuberculosis increased by 28%, that is, there were more than 2,400 cases in just one year5. The incidence of tuberculosis was also reflected in the latest report of the body attached to the United Nations (UN) such that, by the year 2016, the incidence rate in Venezuela was 32 per 100 thousand inhabitants